Filtrasi Air dengan Menggunakan Alat Sederhana untuk Menghasilkan Air Bersih bagi Warga Desa Cikurutug Kecamatan Cireunghas - Yusuf Iskandar; Rani Sri Wahyuni; Rohmat Rohmat; Robi Darwis; Indri Oktaviani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Cikurutug Village, Cireunghas District, Sukabumi Regency, to be precise in RW 1, has problems related to the availability of clean water. The water in the reservoir used by the residents comes from a small river. The water flow is not directly from the mountains or springs but results from soil seepage due to the extensive loosening of the land around the river, resulting in turbid water. This is undoubtedly very dangerous for the health of residents, because of course, it will invite diseases such as dysentery, typhus, and so on. To solve this problem, water filtration is carried out using simple tools that have been designed and then assisted by a water filtration device. The filtration results resulted in an increase in water quality, which would then continue to be used by residents. This filtration device must be maintained to keep the water quality still good.